The Association of Low Skeletal Muscle Mass with Complex Distal Radius Fracture - Oh, Chi Hoon; Kim, Junhyun; Kim, Junhan; Yoon, Siyeong; Jung, Younghoon; Lee, Hyun Il; Choi, Junwon; Lee, Soonchul; Han, Soo Hong (Journal of Clinical Medicine, 2022)
Objectives: Sarcopenia is a skeletal muscle loss disease with adverse outcomes, including falls, mortality, and cardiovascular disease (CVD) in older patients. Distal radius fractures (DRF), common in older people, are strongly related to falls. We aimed to investigate the correlation between DRF and low skeletal muscle mass, which strongly correlated to sarcopenia. Methods: We performed a retrospective review of data from patients diagnosed with or without DRF in our institute between 2015 and 2020. Finally, after propensity score matching, data from 115 patients with and 115 patients without DRF were used for analyses. Multivariate logistic regression analysis was performed for sex, body mass index (BMI), the presence of low skeletal muscle mass, bone quality measured by dual-energy X-ray absorptiometry (DXA), and comorbidities (diabetes mellitus, CVD). Results: We found that female sex (odds ratio = 3.435, p = 0.015), CVD (odds ratio = 5.431, p < 0.001) and low skeletal muscle mass (odds ratio = 8.062, p = 0.001) were significant predictors for DRF. BMI and osteoporosis were not statistically significantly related to DRF. Conclusions: Women with low skeletal muscle mass and CVD may be more responsible for DRF than osteoporosis.
Keywords: distal radius fracture; low skeletal muscle mass; osteoporosis; sarcopenia